A study of the determinants of capital structure based on the US firms in manufacturing industry and utility industry - GAO, LINTONG (2017)
The study focuses on improving an up to date understanding of the determinants of capital structure for US firms in manufacturing and utility industries. 197 firms in manufacturing industry and 191 firms in utility industry are collected in the years 2005 and 2015. The independent variables include tangibility, profitability, growth opportunities, size, liquidity and non-debt tax shields and the independent variable is the leverage ratio. In this study, four cross sectional regression models are estimated separately for manufacturing and utility industries. For each industry the same model are regressed for both 2005 and 2015 in order to compare their coefficients and significances through STATA. The main contribution of this study is that it not only estimates the determinants of capital structure, but also compares the differences of coefficients and significances for two discrete years for two industries separately. Results show that coefficients of tangibility, profitability, growth opportunities, size and liquidity have stronger influence on firms’ leverage, while the non-debt tax shields show less dominance on leverage in utility industries in 2015. In contrast, the coefficient of profitability and size has less effect on the leverage ratios and other coefficients of variables show the same tendency as the utility industry in the manufacturing industry. In addition, the sign of coefficient of tangibility and growth opportunities in manufacturing industry and non-debt tax shields in utility industry are changed in 2015.